Переховування євреїв монахами студійського уставу на взуттєвій фабриці “Солід” у Львові в 1942–1944 рр. - Скіра, Ю. (Lviv Polytechnic Publishing House, 2016)
Описано переховування єврейських родин у підвалах взуттєвої фабрики “Солід” у Львові монахами Студійського Уставу протягом 1942–1944 рр. Викладено історію фабрики і її директора ієромонаха Йоана (Петерса). У другій частині висвітлено становище робітників у львівському гетто, працю євреїв-шевців та їхню втечу з сім’ями у серпні 1942 р. на запрошення студитів. Звернено увагу на питання побуту, небезпек перед якими постали ці люди. Він робить висновок, що переховування такої великої кількості осіб належало до однієї з найскладніших ділянок щодо рятункової акції євреїв, яку проводили монахи-студити за розпорядженням архімандрита Студійського Уставу митрополита Андрея Шептицького. There are still a lot of unsettled questions in studying relations of the Ukrainian Greek Catholic Church and the Jews during the Holocaust. The researchers mainly study the stance of the Metropolitan Andrey Sheptytsky and description of the fates of a certain number of Jews rescued by the clergy. The researchers, however, pay no attention to the facts of rescue of groups of Jews from Lviv Ghetto. There were several cases of such group rescues; this article reveals one of the biggest, as a result of which sixteen people were saved. This happened at the Solid shoe factory, whose director was a German person, Johannes Peters. He entered Univ Holy Dormition Monastery of the Studite Rite. Concealing from the German occupying authority the information about his priestly ordination, he lived secretly as a monk and at the same time remained a lay person on the position of the factory’s director. Knowing about the deaths of the Jews in Lviv Ghetto, he allowed the Studite monks employed by him to hide and shelter the Jewish families. These Jews were shoemakers who worked at the factory from the end of 1941. Monks could not abandon their colleagues, and, therefore, gave them a shelter. Throughout 1942–44 these people secretly worked and lived there. They faced searches and were reported to the police forces by their neighbours. Two Studite monks took care of them, while some lay persons of the Ukrainian Greek-Catholic Church were entrusted to bring meals for them. Hiding such a great number of people was one of the most difficult areas of the Jewish rescue campaign conducted by the Studites under the order of Metropolitan Andrey Sheptytsky, the Archimandrite of the Studite monks. Owing to their consolidated actions, a great self-devotion and courage they managed to save people who were deprived by the Nazis of the right to live.
Keywords: євреї; монахи; фабрика; шевці; переховування; обшуки; гетто; Jews; monks; factory; shoemakers; hide; search; ghetto; 94(477.83-25=411.16):271-789.25-46”1942/1943”